La industria 4.0 y su relación con la Gestión de los Recursos Humanos. - Guerra, R. Pablo; Ortiz, G. Armando (Revista Daena: International Journal of Good Conscience, 2020)
The objective of this research is to discover how the growing Industry 4.0 is evolving the industry as we know it, and how it interacts with the Human Resources area. This revolution, considered the fourth revolution in the history of humanity, is due to a totally technological change, where progress is achieved through software, neural networks, the Internet, which improve the quality of processes in organizations. We will focus on explaining the importance and advances that Industry 4.0 brings in the area of Human Resources, since the profile expected to be achieved in future employees is aimed at these technologies. The entry of this new revolution will bring with it the constant development of artificial intelligence, software development, automation, big data, among others, which in turn brings a new recruitment profile in the management, implementation and maintenance of these technologies.